Association between metabolic score for insulin resistance and lower limb pain among the elderly: a cross-sectional study - Hu, Yanfen; Yu, Junxia; Xu, Zhenjie; Gao, Yan; Li, Yang; Li, Lingxia (Frontiers in Endocrinology, 2025)
PurposeThis study aims to investigate the association between the metabolic score for insulin resistance (Mets-IR) and lower limb pain (LLP) among the elderly.MethodsBaseline and follow-up data were collected from the China Health and Retirement Longitudinal Study (CHARLS) database in 2011 and 2018, respectively. Multivariable logistic regression analysis and restricted cubic spline were performed to explored the relationship between Mets-IR and LLP. Subgroup analysis was also conducted.ResultsA total of 4983 participants were included in the study, among which 3350 (67.2%) suffered from LLP. Logistic regression analysis confirmed a statistically significant relationship between Mets-IR and LLP risk (p < 0.001). Restricted cubic spline plots indicated that the association between Mets-IR and LLP is not nonlinear. Both subgroup and interaction analyses hinted at the influence of variation in sleep duration on this correlation.ConclusionsThe findings indicate a positive correlation between Mets-IR and LLP risk, which is influenced reciprocally by sleep duration.